Aetiologies and therapeutic management of infertility in cows reared in high altitude tribal areas of Himachal Pradesh - SHARMA, ANKITA; SINGH, MADHUMEET; SHARMA, AKSHAY; KUMAR, PRAVESH (The Indian Journal of Animal Sciences, 2022)
Infertile cows (664) reared in different tribal areas of Himachal Pradesh were examined thoroughly by rectal examination during infertility treatment camps and diagnosis of reproductive ailments was done to document the prevalence of different types of infertility. The highest prevalence was recorded for anestrus (44.27%) followed by endometritis (42.77%) and miscellaneous reproductive disorders (6.77%). Highest prevalence of anestrus conditions was recorded in Bharmour (51.72%) followed by Kinnaur (49.05%), Lahaul (47.76%) and Spiti (45.39%) areas whereas, lowest prevalence was recorded in Pangi (27.93%) region. After diagnosis, 189 cows were treated for different reproductive ailments; however, only 101 cows could be followed, and 70 responded to the treatment with success rate of 69.30%. Anestrus and endometritis were the most prevalent forms of infertility in cows of tribal areas and were successfully treated with their respective treatment regimen.